2019
DOI: 10.3390/biomedicines7010018
|View full text |Cite
|
Sign up to set email alerts
|

Daclizumab: Mechanisms of Action, Therapeutic Efficacy, Adverse Events and Its Uncovering the Potential Role of Innate Immune System Recruitment as a Treatment Strategy for Relapsing Multiple Sclerosis

Abstract: Daclizumab (DAC) is a humanized, monoclonal antibody that blocks CD25, a critical element of the high-affinity interleukin-2 receptor (IL-2R). DAC HYP blockade of CD25 inhibits effector T cell activation, regulatory T cell expansion and survival, and activation-induced T-cell apoptosis. Because CD25 blockade reduces IL-2 consumption by effector T cells, it increases IL-2 bioavailability allowing for greater interaction with the intermediate-affinity IL-2R, and therefore drives the expansion of CD56bright natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 81 publications
(132 reference statements)
0
40
0
3
Order By: Relevance
“…at present, there is no anti-TSlP antibody approved by the uS Food and drug administration (32). as a therapeutic antibody, affinity is the most important characteristic (33). In the present study, an anti-TSlP-scFv-Fc recombinant antibody was successfully constructed and its affinity was increased using dS 4.5 software.…”
Section: Discussionmentioning
confidence: 99%
“…at present, there is no anti-TSlP antibody approved by the uS Food and drug administration (32). as a therapeutic antibody, affinity is the most important characteristic (33). In the present study, an anti-TSlP-scFv-Fc recombinant antibody was successfully constructed and its affinity was increased using dS 4.5 software.…”
Section: Discussionmentioning
confidence: 99%
“…Low doses of IL-2 have been successfully employed as add-on MS therapy [10], while the detection of increased IL-2 levels in MS patients has led to the development of therapeutic approaches targeting IL-2 receptor [11]. However, further observations have demonstrated that side effects such as severe inflammatory brain disorders [12,13] and resistance to antagonistic antibody therapies that target receptors at the cell surface may arise in a relatively short time [14]. Moreover, high expression of IL-2 has been reported in animals after Mycobacterium tuberculosis and MAP infection [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Daclizumab is a humanized monoclonal antibody that irreversibly blocks CD25, preventing signaling through the high affinity IL-2R while increasing IL-2 bioavailability to bind to the low affinity receptor (reviewed in (Cohan et al 2019;Bielekova 2019)). Due to the complex roles of IL-2 in vivo, daclizumab induces several immunological changes, including inhibition of T cell activation, reduction in the frequency and survival of regulatory T cells, and expansion of CD56 bright NK cells (Cohan et al 2019;Bielekova 2019). It was originally developed as an intravenous treatment for several disease indications, including the prevention of transplant rejection and the treatment of severe uveitis and T cell leukemia (Cohan et al 2019;Bielekova 2019).…”
mentioning
confidence: 99%
“…Due to the complex roles of IL-2 in vivo, daclizumab induces several immunological changes, including inhibition of T cell activation, reduction in the frequency and survival of regulatory T cells, and expansion of CD56 bright NK cells (Cohan et al 2019;Bielekova 2019). It was originally developed as an intravenous treatment for several disease indications, including the prevention of transplant rejection and the treatment of severe uveitis and T cell leukemia (Cohan et al 2019;Bielekova 2019). Later a subcutaneous form (daclizumab beta) was developed and approved for the treatment of relapsing forms of multiple sclerosis (RMS) due to its beneficial effects including reduction in lesion size and slowed disease progression (Bielekova et al 2006(Bielekova et al , 2009Elkins et al 2015;Wynn et al 2010;Elkins et al 2012); (Gold et al 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation